Exploration and Characterization of Chitinolytic Bacteria from Leachate, Shrimp Pond Water and Rhizosphere Roots - Aisyah Aisyah; Zia Nurfauziah; Adila Nursidik; Anasi Faisal Sukiyas; Diva Tari Asina Munthe; Gilang Vaza Benatar (Jurnal Biologi Tropis, 2023)
Chitinase enzymes are enzymes that can hydrolyze chitin polymers into chitin oligosaccharides or N-acetylglucosamine synergistically and sequentially. This enzyme is naturally produced by bacteria, fungi, plants, and animals. The magnitude of the potential possessed by chitinolytic bacteria with their living environment spread in various sources, does not rule out the possibility of isolating chitinolytic bacteria from leachate water, shrimp pond water, and rhizosper root soil. This study aims to isolate and identify the morphology of chitinolytic bacterial colonies obtained from the exploration results. The research was conducted with the exploration method and then analyzed descriptively. The results of the study obtained 22 isolates of chitinolytic bacteria from the exploration results with 11 isolates with the code TAC is an isolate from the roots of chili soil, 8 isolates with the code ALT comes from leachate water, and 3 isolates from shrimp ponds coded TUC. The results of morphological observations of bacterial colonies obtained the cell shape of the bacterial colonies were 17 cocci and only 5 were bacilli. Isolates are mostly white with milky white and bone white color and 7 isolates with red and yellow color variations. The results of gram staining showed 10 bacterial isolates were gram negative and 12 isolates were positive with bacterial cell shape mostly cocci.